Role of situational data flow processing for afferent synthesis of motor responses in boxing - Kolesnik, I. S.; Osipov, D. A.; Gatin, F. A. (Theory and Practice of Physical Culture, 2019)
The study offers a new afferent synthesizing skills building and sport excellence method to improve efficiency of the boxing training systems in application to 13-14 year-old boxers of mass sport qualifications. The new model designed and offered by the authors is driven by the afferent synthesis of attacking and defensive actions with their key elements. The synthesis gives the means to set mission and goals in the training process based on the general athletic training and education process principles; and find facilitating provisions for and factors of influence on the afferent synthesizing skills building process. The skills excelling method includes a set of special exercises; creative physical practices; special education system; and a set of the motor skills rating criteria.